Neuroprotective Effects of Lycium barbarum Berry on Neurobehavioral Changes and Neuronal Loss in the Hippocampus of Mice Exposed to Acute Ionizing Radiation - Guo, Lei (SAGE Publications, 2021)
10.1177/15593258211057768